Fabrication of hybrid magnetic HKUST-1 and its highly efficient adsorption performance for Congo red dye1. Issue 25 (21st March 2015) - Xu, Yan; Jin, Jingjie; Li, Xianliang; Han, Yide; Meng, Hao; Wang, Tianyu; Zhang, Xia
<x xml:space="preserve">Abstract</x> A hybrid magnetic metal–organic framework HKUST-1 synthesized via chemical bonding approach possesses efficient and recyclable adsorption performance for Congo red.